2019
DOI: 10.1097/cm9.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Taurine on the proliferation and apoptosis of human cervical carcinoma cells and its mechanism

Abstract: Background: Cervical cancer has the fourth highest incidence and mortality rate of all cancers in women worldwide; it seriously harms their physical and mental health. The aim of this study was to observe the roles and preliminary mechanism of Taurine (Tau)-induced apoptosis in cervical cancer cells. Methods: Cells from the human cervical cancer cell line SiHa were transfected with the recombinant plasmid pEGFP-N1-MST1 (mammalian sterile 20-like kinase 1); then, the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…ATP plays a critical role in early apoptosis as it interacts with apoptotic protease activating factor 1 (Apaf-1) before activation of the caspase cascade pathway [ 34 ]. Previous reports suggested that taurine induced apoptosis in many types of cancers [ 35 , 36 ]. However, the exposure of taurine can suppress the apoptosis in cardiomyocyte by inhibition interaction between apaf-1 and caspase-9 to form apoptosomes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATP plays a critical role in early apoptosis as it interacts with apoptotic protease activating factor 1 (Apaf-1) before activation of the caspase cascade pathway [ 34 ]. Previous reports suggested that taurine induced apoptosis in many types of cancers [ 35 , 36 ]. However, the exposure of taurine can suppress the apoptosis in cardiomyocyte by inhibition interaction between apaf-1 and caspase-9 to form apoptosomes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taurine functions as a redox-directed agent to specifically target tumor cells, raising the possibilities to achieve drug selectivity without off-target toxicity. Several cases have proved that taurine displays strong growth-inhibitory effect on multiple cancer types including colon cancer ( 42 , 43 ), lung cancer ( 44 ), hepatocarcinoma ( 30 ), pancreatic cancer ( 45 ), glioma ( 46 ), melanoma ( 47 ) breast cancer ( 48 - 51 ), nasopharyngeal carcinoma (NPC) ( 52 ), prostate cancer ( 53 , 54 ) and ovarian cancer ( 55 , 56 ).…”
Section: The Role Of Taurine In Inflammationmentioning
confidence: 99%
“…Additionally to the functional significance of taurine in the diagnosis of bladder cancer, it has been suggested that taurine was effective in forestalling the proliferation of cervical cancer (CC) SiHa cells, through induction of apoptosis. The underlying molecular mechanism of taurine was based on upregulation of MST1 signaling pathway signaling pathway, leading to increased p53 nuclear transcriptional translocation ( 55 ).…”
Section: The Role Of Taurine In Inflammationmentioning
confidence: 99%
“…Tau is involved in osmoregulation, the modulation of protein phosphorylation, calcium ion regulation, anti-oxidant response, membrane stabilization, bile acid conjugation, lipid metabolism, glucose regulation [ 20 ]. Tau displays a strong growth-inhibitory effect on multiple cancer types including colon cancer [ 21 , 22 ], lung cancer [ 23 ], hepatocarcinoma [ 24 ], pancreatic cancer [ 25 ], glioma [ 26 ], melanoma [ 27 ], breast cancer [ 28 , 29 , 30 , 31 ], nasopharyngeal carcinoma [ 32 ], prostate cancer [ 33 , 34 ] and ovarian cancer [ 35 ]. Additionally, Tau has been shown to attenuate the toxic side effects of classical chemotherapeutic drugs (doxorubicin, 5-fluorouracil, cis-platin, tamoxifen), thereby enhancing their therapeutic efficacy [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%